Effect of butanolic fraction of yellow and black maca (Lepidium meyenii) on the sperm count of adult mice - Inoue, N (2016)
The effects of butanol/aqueous fractions partitioned from methanol extract of yellow and black maca were examined. Total phenolic content (TPC) and antioxidant capacity by 2,2′-diphenyl-1-picrylhydrazyl were used to evaluate maca fractions in vitro. Daily sperm production and sperm count in epididymis and vas deferens in mice were determined as biological effect of maca extracts in vivo. Yellow maca had better antioxidant capacity than black maca. TPC is higher in the aqueous fraction than in the methanolic extract of yellow or black maca. Black maca administration resulted in higher concentration of sperm count in epididymis and vas deferens compared to yellow maca. In conclusion, better biological effect was observed in the methanolic extract of maca than in its partitioned fractions.